Cannabidiol Modulates the Immunophenotype and Inhibits the Activation of the Inflammasome in Human Gingival Mesenchymal Stem Cells - Libro, Rosaliana; Scionti, Domenico; Diomede, Francesca; Marchisio, Marco; Grassi, Gianpaolo; Pollastro, Federica; Piattelli, Adriano; Bramanti, Placido; Mazzon, Emanuela; Trubiani, Oriana (Frontiers in Physiology, 2016)
Human Gingival Mesenchymal Stem Cells (hGMSC) are multipotential cells that can expand and differentiate in culture under specific and standardized conditions. In the present study, we have investigated whether in vitro pre-treatment of hGMCs with Cannabidiol (CBD) can influence their expression profile, improving the therapeutic potential of this cell culture. Following CBD treatment (5μM) for 24 h, gene expression analysis through Next Generation Sequencing (NGS) has revealed several genes differentially expressed between CBD-treated hGMCs (CBD-hGMCs) and control cells (CTR-hGMCs) that were linked to inflammation and apoptosis. In particular, we have demonstrated that CBD treatment in hGMCs prevented the activation of the NALP3-inflammasome pathway by suppressing the levels of NALP3, CASP1 and IL18, and in parallel, inhibited apoptosis, as demonstrated by the suppression of Bax. CBD treatment was also able to modulate the expression of the well-known mesenchymal stem cell markers (CD13, CD29, CD73, CD44, CD90 and CD166), and other surface antigens. Specifically, CBD led to the downregulation of genes codifying for antigens involved in the activation of the immune system (CD109, CD151, CD40, CD46, CD59, CD68, CD81, CD82, CD99), while it led to the upregulation of those implicated in the inhibition of the immune responses (CD47, CD55, CD276). In conclusion, the present study will provide a new simple and reproducible method for preconditioning hGMSCs with CBD, before transplantation, as an interesting strategy for improving the hGMCs molecular phenotype, reducing the risk of immune or inflammatory reactions in the host, and in parallel, for increasing their survival and thus, their long-term therapeutic efficacy.